Latent Class Analysis of the CBCL Dysregulation Profile for 6- to 16-Year-Olds in 29 Societies. Issue 5 (3rd September 2021) - Rescorla, Leslie A.; Jordan, Phoebe; Zhang, Susu; Baelen-King, Grace; Althoff, Robert R.; Ivanova, Masha Y.; International ASEBA Consortium,
ABSTRACT: Objective : We used latent class analysis (LCA) to examine the prevalence and characteristics of the Dysregulation Profile (DP) based on data from the Child Behavior Checklist for Ages 6–18. The DP comprises elevated scores on the Anxious/Depressed, Attention Problems, and Aggressive Behavior syndromes and thus reflects significant problems in self-regulation of mood, attention, and behavior. Method : We examined CBCL data for 56, 666 children ages 6 to 16 in 29 societies, many of which are countries but some of which are not (e.g., Hong Kong, Puerto Rico). The 29 societies varied widely in race/ethnicity, religion, geographic location, political/economic system, and population size. Results : The various statistical indices for good LCA model fit, while not always consistent, supported a DP class in every society. The omnicultural mean probability of assignment to the DP class (mean of the societal means) was 93% ( SD = 2.4%). Prevalence of the DP class ranged from 2% to 18% across societies, with an omnicultural mean prevalence of 9%. In every society, the DP class had significantly higher scores than the pooled non-DP classes on all three DP syndromes. The 8-syndrome T score profile for the DP class in many societies featured elevations on all eight CBCL syndromes. Conclusions : Although the same instrument, analytic procedures, and decision rules were used in these 29 samples, model fit, the number of classes, and the prevalence of the DP class varied across societies. High scores on the three DP syndromes often co-occurred with high scores on most other CBCL syndromes.